Grammar of the Sentani Language - Cowan, H. (Brill, 1965)
Indonesia
English
Keywords: Asian history; indonesia; Affix; Aorist; Gerund; Grammatical aspect; Inflection; Object (grammar); Phoneme; Preposition and postposition; Verb; Vowel